2017
DOI: 10.1021/acschembio.7b00052
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Frameshift RNA-Targeted Triazoles Inhibit Propagation of Replication-Competent and Multi-Drug-Resistant HIV in Human Cells

Abstract: The HIV-1 frameshift-stimulating (FSS) RNA, a regulatory RNA of critical importance in the virus’ life cycle, has been posited as a novel target for anti-HIV drug development. We report the synthesis and evaluation of triazole-containing compounds able to bind the FSS with high affinity and selectivity. Readily accessible synthetically, these compounds are less toxic than previously reported olefin congeners. We show for the first time that FSS-targeting compounds have antiviral activity against replication-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Small molecules that strongly target a specific RNA are uncommon, and these are likely to engage multiple unintended partners (91). At the outset of screening, effective approaches strive to limit off-target recognition by conducting binding assays in the presence of a molar excess of tRNA (85), or by gauging nonspecific binding by use of decoy RNAs (85, 86), RNase footprinting (110), or whole transcriptome analysis (111). Even after the identification of a tight-binding RNA inhibitor, the structure determination of such a complex is even more extraordinary.…”
Section: Model Ncrna-inhibitor Interactions: Base Pairing and Shape Cmentioning
confidence: 99%
“…Small molecules that strongly target a specific RNA are uncommon, and these are likely to engage multiple unintended partners (91). At the outset of screening, effective approaches strive to limit off-target recognition by conducting binding assays in the presence of a molar excess of tRNA (85), or by gauging nonspecific binding by use of decoy RNAs (85, 86), RNase footprinting (110), or whole transcriptome analysis (111). Even after the identification of a tight-binding RNA inhibitor, the structure determination of such a complex is even more extraordinary.…”
Section: Model Ncrna-inhibitor Interactions: Base Pairing and Shape Cmentioning
confidence: 99%
“…The binders with highest affinity were thus enriched and then isolated, characterized, and validated for RNA-binding. After replacing the disulfide linkage with more stable bioisosteres, the method yielded bioactive ligands for two RNAs of known structure: DM1 r(CUG) exp , where statistically significant improvements in splicing were observed in mouse models ( 70 ), and HIV-1 frameshift-stimulating RNA, ( 71 , 72 ) where in one example the decrease in viral infectivity (EC 50 values of 3.9 and 26 μM) correlated to frame-shifting activity (>50% at 50 μM) in cell culture ( 73 ). A powerful advantage of DCC is that multivalent ligands can be constructed without knowledge of the RNA structure, including larger and complex tertiary folds.…”
Section: Discovery and Design Of Rna-targeted Multivalent Chemical Prmentioning
confidence: 99%
“…RNA-specific reporter systems were occasionally used to confirm on-target effects, including fusion-induced gene stimulation ( 79 ), heterologous tethering ( 54 ), and a viral protein reporter ( 48 ). A noteworthy example of assessing off-target effects was the use of RNA-Seq at increasing ligand concentrations in the absence of the target RNA ( 72 ). The experiment in HEK293T cells revealed that 53 of the 17 822 transcripts assayed had statistically significant alterations at two concentrations, potentially reflecting a cellular stress response.…”
Section: Chemical Probe Characterizationmentioning
confidence: 99%
“…Viral RNA elements have been identified as antiviral targets due to conservation of sequence and functions that are distinguishable from the host (Panjaworayan and Brown, 2011 ; Chen et al, 2014 ; Cardno et al, 2015 ; Le Grice, 2015 ; Hermann, 2016 ; Hilimire et al, 2017 ). For example, the internal ribosome entry sites (IRES) of hepatitis C virus (HCV) is targeted by benzimidazole (Dibrov et al, 2012 ).…”
Section: Know Your Enemymentioning
confidence: 99%